2017
DOI: 10.1371/journal.pone.0186331
|View full text |Cite
|
Sign up to set email alerts
|

XX Disorder of Sex Development is associated with an insertion on chromosome 9 and downregulation of RSPO1 in dogs (Canis lupus familiaris)

Abstract: Remarkable progress has been achieved in understanding the mechanisms controlling sex determination, yet the cause for many Disorders of Sex Development (DSD) remains unknown. Of particular interest is a rare XX DSD subtype in which individuals are negative for SRY, the testis determining factor on the Y chromosome, yet develop testes or ovotestes, and both of these phenotypes occur in the same family. This is a naturally occurring disorder in humans (Homo sapiens) and dogs (C. familiaris). Phenotypes in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 98 publications
0
22
1
Order By: Relevance
“…Studies on the methylation of WNT4 gene showed that methylation was similar in XX DSD and control dogs [30], suggesting that this may not be an adequate candidate gene for the XX DSD syndrome in dogs. Still, a decreased transcription of WNT4 was reported in XX DSD embryos using a genome wide association study and whole genome sequencing [13]. The same study describes a decrease in RSPO1 and FOXL2 expression, demonstrating that the ovary determining genes are downregulated in canine gonads from embryos at risk of XX DSD, while the testicular determining genes (namely the SOX9 and FGF9) are up-regulated [13].…”
Section: Loss Of Function Of Wnt4/rspon1/-catenin and Foxl2 Pathwaysmentioning
confidence: 83%
See 1 more Smart Citation
“…Studies on the methylation of WNT4 gene showed that methylation was similar in XX DSD and control dogs [30], suggesting that this may not be an adequate candidate gene for the XX DSD syndrome in dogs. Still, a decreased transcription of WNT4 was reported in XX DSD embryos using a genome wide association study and whole genome sequencing [13]. The same study describes a decrease in RSPO1 and FOXL2 expression, demonstrating that the ovary determining genes are downregulated in canine gonads from embryos at risk of XX DSD, while the testicular determining genes (namely the SOX9 and FGF9) are up-regulated [13].…”
Section: Loss Of Function Of Wnt4/rspon1/-catenin and Foxl2 Pathwaysmentioning
confidence: 83%
“…Albeit a duplication of the SOX9 coding region has been found in two dogs diagnosed as XX;SRY-negative [69], some studies demonstrated that other individuals do not present SOX9 duplication [21,70]. Conversely, duplication [15] or copy variations [13] of a region upstream of the SOX9 gene have been identified in XX;SRY-negative dogs. Two highly polymorphic copy number variable regions have been identified in upstream regions to the canine SOX9 gene; one of those being at a similar distance from the SOX9 as that of the human RevSex [29].…”
Section: Gain Of Function Of Sox9mentioning
confidence: 99%
“…XX DSD has been diagnosed in over 40 breeds, with elevated incidence being seen in American Cocker Spaniels, English Cocker Spaniels, and Kerry Blue Terriers [Meyers-Wallen et al, 2017], as well as in French Bulldogs and American Staffordshire terriers [Nowacka-Woszuk et al, 2019]. The earliest cases in French bulldogs were described in 2011 [Campos et al, 2011;Silversides et al, 2011], and the numbers increased over the following years, reaching at least 14 cases.…”
mentioning
confidence: 99%
“…Our results are similar to those of Nowacka et al (2005) in the 78, XX SRY-negative dogs of American Staffordshire terrier. To reveal the causative mutation of XX DSD in dogs, extensive effort has been initiated for many years (Meyers-Wallen et al, 2017;Meyers-Wallen, 2012;Nowacka-Woszuk et al, 2017;Pujar, Kothapalli, Göring, & Meyers-Wallen, 2007;Rossi et al, 2014;Switonski et al, 2011). Although until today, the molecular background of XX DSD (78, XX; SRY-negative) is not fully recognized, it is assumed to be linked to the copy number variation (CNV) in the region harbouring the SOX9 gene.…”
Section: Sequencing Resultsmentioning
confidence: 99%
“…Authors have supposed that multiplication of this element may alter expression of the SOX9 gene, triggering the DSD phenotype. At present, it has also been assumed that an epigenomic model for gonadal mosaicism in the canine XX DSD could account for the wide range of XX DSD phenotypes observed in related individuals (Meyers‐Wallen et al, ). The authors identified significant RSPO1 down‐regulation in embryonic gonads at risk of canine XX DSD, without significant up‐regulation of SOX9 or other known testis pathway genes supposing that molecular lesions acting upstream of RSPO1 induce epigenomic gonadal mosaicism.…”
Section: Discussionmentioning
confidence: 99%